Impact of organizational innovation on firm performance: evidence from Malaysian-Based ICT Companies - Salem, Isam Mohamed; Sulaiman, Mohamed (Global Research Society, 2011)

(untitled)
This empirical study attempts to investigate the effect of organizational innovation on company performance. Based on the literature review, the study hypothesizes that organizational innovation is positively related to company performance, which is measured in terms of both market and financial metrics. Data was collected via electronic survey from 115 small and medium enterprises operating in the ICT industry in Malaysia. Findings from the study support both the hypothesis that organizational innovation has a significant influence on firm performance. The study therefore contributes to the existing body of literature on innovation-performance link, and several guidelines and practical implications from the study are also discussed.